(untitled) (Aintelia Science Notes, 2024)
In this study, a charging station based on renewable energy sources has been designed for e-bikes, which have been widely used around the world in recent years. Due to the nature of renewable energy sources, all calculations should be done according to the region where these systems will be installed. In this study, the province of Van was selected as the region for the photovoltaic system-based charging station design, and the meteorological and solar data of this province were used. Calculations are completed using the technical specifications of an e-bike model that is commercially available, which can be defined as the load for the designed charging system. The mathematical models required for the design were proposed, the results were discussed and suggestions were presented.